Development of a lean maturity assessment model using interval-valued spherical fuzzy AHP method - Alper Kiraz; Asiye Yücedag Gürel (International Journal of Research in Industrial Engineering)
Continuously adding value to a company's products and services is inevitable in adapting to this evolving and challenging global market. That is why lean philosophy is becoming increasingly important and popular among companies, and they are relying more and more on it. It not only assists in increasing profitability and quality by eliminating all processes that provide no value to the customer but also enables increased flexibility in production and productivity. In this study, the criteria affecting the Lean Maturity Level (LML) were determined, and a lean maturity measurement model, which helps companies define and understand the level of lean maturity and lean effectiveness, was developed. A recently completed case study included data from an online survey with 116 questions, which were conducted on 187 middle to senior-level professionals in Türkiye from different industries. In this model, 9 main and 14 sub-lean criteria were generated to determine LML , and each criterion was weighted based on the assessments of experts. In this paper, the interval-valued spherical fuzzy AHP method is applied for the very first time to the weighting of the criteria of a lean maturity assessment model. After collecting data through an online survey study, Confirmatory Factor Analysis (CFA) in the IBM SPSS AMOS V26 program was applied to test the model fit, validity, and reliability. To determine the LMLs, the leveling scale (understanding, implementation, improvement, and sustainability) was used from the model for LMLs in manufacturing cells. As a result of the analysis of the survey results obtained from the participating companies, the overall LML was calculated as 2.55 out of 4. This result corresponds to the level 3 - improvement range on the leveling scale. The lean maturity success rate of surveyed companies was set at 64%.